2017
DOI: 10.3892/mmr.2017.6346
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tim-3 reduces Helicobacter pylori-associated inflammation through TLR4/NFκB signaling in vitro

Abstract: The present study aimed to investigate the interaction between T-cell immunoglobulin and mucin-domain-containing molecule-3 (Tim-3) and Toll-like receptor 4 (TLR4)/nuclear factor κB (NF‑κB) signaling in Helicobacter pylori-infected RAW264.7 macrophage cells. RAW264.7 cells were co‑cultured with H. pylori SS1 at different bacteria/cell ratios, and subsequently the mRNA expression of Tim‑3, TLR4, and myeloid differentiation factor 88 (MyD88) was measured by reverse transcription-quantitative polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Those inflammatory factors can be secreted by gastric epithelial cells and play a major role in triggering the mucosal inflammatory damage caused by H. pylori [44,45]. In addition, H. pylori and its virulence factors are capable of increasing the production of the inflammatory mediators TNF-α, IL-6, and IFN-γ by macrophages, which contribute to the amplification of the inflammatory response in the gastric mucosa [46,47]. In our previous study [17], we demonstrated that L. fermentum UCO-979C significantly reduced the production of IL-8, TNF-α, IL-6, and MCP-1 in AGS cells and macrophages challenged with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those inflammatory factors can be secreted by gastric epithelial cells and play a major role in triggering the mucosal inflammatory damage caused by H. pylori [44,45]. In addition, H. pylori and its virulence factors are capable of increasing the production of the inflammatory mediators TNF-α, IL-6, and IFN-γ by macrophages, which contribute to the amplification of the inflammatory response in the gastric mucosa [46,47]. In our previous study [17], we demonstrated that L. fermentum UCO-979C significantly reduced the production of IL-8, TNF-α, IL-6, and MCP-1 in AGS cells and macrophages challenged with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous in vitro studies also revealed the ability of the UCO-979C strain to improve the levels of IL-10 in H. pylori-infected macrophages [17], which is in line with the increased concentrations of IL-10 found in gastric and serum samples of H. pylori-infected mice. Increased levels of IL-10 may contribute to the chronicity of gastritis, however, this regulatory cytokine is of fundamental importance to prevent mucosal injury mediated by the inflammatory response [47][48][49][50]. Then, the balance in the inflammatory and regulatory cytokine production induced by L. fermentum UCO-979C could offer advantages in the protection against H. pylori infection, since a reduced inflammatory damage was observed in the histopathological analysis of gastric samples of mice.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori has been described to induce an enhanced M1-like phenotype ( Quiding-Jarbrink et al, 2010 ; Borlace et al, 2011 ; Fehlings et al, 2012 ; Gobert et al, 2014 ; Moyat and Velin, 2014 ), representing the expression of iNOS, which would induce NO to combat H. pylori infection ( Kaparakis et al, 2008 ; Gobert and Wilson, 2016 ; Hardbower et al, 2017 ). M1 macrophages highly express pro-inflammatory cytokines such as IL-1β, IL-6, IL-12p70, TNF-α, and IFN-γ ( Lewis et al, 2011 ; Liao et al, 2016 ; Wang et al, 2017 ; Gebremariam et al, 2019 ). Activation of immune responses by host macrophages upon H. pylori infection requires the involvement of a variety of signaling events such as NF-κB and MAPK ( Gobert and Wilson, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 may play a role in gastric immunologic response to H. pylori (29,30). We hypothesized that MyD88 expression correlates with H. pylori infection.…”
Section: Correlation Between Myd88 Expression and H Pylori Infectionmentioning
confidence: 99%